Step
*
5
of Lemma
Taylor-remainder-as-integral
1. I : Interval
2. iproper(I)
3. a : ℝ
4. a ∈ I
5. b : ℝ
6. b ∈ I
7. [rmin(a;b), rmax(a;b)] ⊆ I 
8. n : ℕ
9. ∀F:ℕ2 ⟶ I ⟶ℝ
     ((∀k:ℕ2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y))))
     
⇒ finite-deriv-seq(I;1;i,x.F i x)
     
⇒ (Taylor-remainder(I;0;b;a;k,x.F k x) = a_∫-b (F 1 t/r1) * r1 dt))
10. ∀n:{n:ℤ| 0 < n} 
      ((∀F:ℕ(n - 1) + 2 ⟶ I ⟶ℝ
          ((∀k:ℕ(n - 1) + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y))))
          
⇒ finite-deriv-seq(I;(n - 1) + 1;i,x.F i x)
          
⇒ (Taylor-remainder(I;n - 1;b;a;k,x.F k x) = a_∫-b (F ((n - 1) + 1) t/r((n - 1)!)) * b - t^n - 1 dt)))
      
⇒ (∀F:ℕn + 2 ⟶ I ⟶ℝ
            ((∀k:ℕn + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y))))
            
⇒ finite-deriv-seq(I;n + 1;i,x.F i x)
            
⇒ (Taylor-remainder(I;n;b;a;k,x.F k x) = a_∫-b (F (n + 1) t/r((n)!)) * b - t^n dt))))
11. n1 : ℕ
12. F : ℕn1 + 2 ⟶ I ⟶ℝ
13. ∀k:ℕn1 + 2. ∀x,y:{a:ℝ| a ∈ I} .  ((x = y) 
⇒ ((F k x) = (F k y)))
14. finite-deriv-seq(I;n1 + 1;i,x.F i x)
15. x : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
16. y : {x:ℝ| x ∈ [rmin(a;b), rmax(a;b)]} 
17. x = y
⊢ ((F (n1 + 1) x/r((n1)!)) * b - y^n1) = ((F (n1 + 1) y/r((n1)!)) * b - y^n1)
BY
{ ((Assert (F (n1 + 1) x) = (F (n1 + 1) y) BY Auto) THEN RWO "-1" 0 THEN Auto) }
Latex:
Latex:
1.  I  :  Interval
2.  iproper(I)
3.  a  :  \mBbbR{}
4.  a  \mmember{}  I
5.  b  :  \mBbbR{}
6.  b  \mmember{}  I
7.  [rmin(a;b),  rmax(a;b)]  \msubseteq{}  I 
8.  n  :  \mBbbN{}
9.  \mforall{}F:\mBbbN{}2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
          ((\mforall{}k:\mBbbN{}2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y))))
          {}\mRightarrow{}  finite-deriv-seq(I;1;i,x.F  i  x)
          {}\mRightarrow{}  (Taylor-remainder(I;0;b;a;k,x.F  k  x)  =  a\_\mint{}\msupminus{}b  (F  1  t/r1)  *  r1  dt))
10.  \mforall{}n:\{n:\mBbbZ{}|  0  <  n\} 
            ((\mforall{}F:\mBbbN{}(n  -  1)  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
                    ((\mforall{}k:\mBbbN{}(n  -  1)  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y))))
                    {}\mRightarrow{}  finite-deriv-seq(I;(n  -  1)  +  1;i,x.F  i  x)
                    {}\mRightarrow{}  (Taylor-remainder(I;n  -  1;b;a;k,x.F  k  x)
                          =  a\_\mint{}\msupminus{}b  (F  ((n  -  1)  +  1)  t/r((n  -  1)!))  *  b  -  t\^{}n  -  1  dt)))
            {}\mRightarrow{}  (\mforall{}F:\mBbbN{}n  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
                        ((\mforall{}k:\mBbbN{}n  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y))))
                        {}\mRightarrow{}  finite-deriv-seq(I;n  +  1;i,x.F  i  x)
                        {}\mRightarrow{}  (Taylor-remainder(I;n;b;a;k,x.F  k  x)  =  a\_\mint{}\msupminus{}b  (F  (n  +  1)  t/r((n)!))  *  b  -  t\^{}n  dt))))
11.  n1  :  \mBbbN{}
12.  F  :  \mBbbN{}n1  +  2  {}\mrightarrow{}  I  {}\mrightarrow{}\mBbbR{}
13.  \mforall{}k:\mBbbN{}n1  +  2.  \mforall{}x,y:\{a:\mBbbR{}|  a  \mmember{}  I\}  .    ((x  =  y)  {}\mRightarrow{}  ((F  k  x)  =  (F  k  y)))
14.  finite-deriv-seq(I;n1  +  1;i,x.F  i  x)
15.  x  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
16.  y  :  \{x:\mBbbR{}|  x  \mmember{}  [rmin(a;b),  rmax(a;b)]\} 
17.  x  =  y
\mvdash{}  ((F  (n1  +  1)  x/r((n1)!))  *  b  -  y\^{}n1)  =  ((F  (n1  +  1)  y/r((n1)!))  *  b  -  y\^{}n1)
By
Latex:
((Assert  (F  (n1  +  1)  x)  =  (F  (n1  +  1)  y)  BY  Auto)  THEN  RWO  "-1"  0  THEN  Auto)
Home
Index